Keseimbangan Angka Kelahiran dan Kematian dalam Menjaga Stabilitas Penduduk di Desa Cikuya - Rizky Nurul Izzati; Siti Nurhalizah; Akrom Akrom (Jurnal Riset Multidisiplin Edukasi, 2026)
This study analyzes the balance between birth and death rates and its impact on population stability in Cikuya Village, Solear District, Tangerang Regency. Using a descriptive qualitative approach with secondary data from the village office and community health center, the study found a significant imbalance between an average birth rate of 310 babies per year and a death rate of only 115 people per year, resulting in a natural population surplus of 195 people annually. This imbalance is caused by the low age of first marriage for women at 17.8 years, family planning participation of only 41 percent, and the success of health programs that have reduced mortality rates. The impacts include conversion of rubber forest land, clean water crisis, school overcapacity, youth unemployment reaching 27 percent, and an increase in poverty from 12 percent to 22 percent. This study recommends strengthening family planning programs, socializing the ideal age for marriage, and developing agro-tourism as efforts to achieve population balance.